Initial Study of Intrusion on The Serambi Nusantara Coast Using Geoelectrical Methods - Delianti, Delianti; Choerullah, Andy; Muslim, Anis Aulia (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
The Serambi Nusantara area, based on geological conditions, has alluvial formations with sand that almost dominates, interspersed with clay rock throughout the location with swamp conditions in most parts of the area. Morphologically, Serambi Nusantara is a coastal area. Most of the population in this area uses groundwater to meet their water needs due to the increasing intensity of use so groundwater is decreasing and there is emptiness in the well cavities, this results in seawater seeping from these cavities and mixing with groundwater which causes water problems in this area, especially the salinity of the water quality. This research was carried out to determine the quality of groundwater using the Induction Polarization (IP) method, in the Serambi Nusantara area where the research stage included geological mapping of the area with results according to the description above, checking water quality data and geoelectric measurements of induced Polarization (IP). In the research results, it was found that the cross-sectional chargeability value at a depth of ± 20 m showed low chargeability (-10 msec), indicating an indication of seawater intrusion in the research area. This value is similar to previous research.